2013
DOI: 10.1007/s00264-013-1875-8
|View full text |Cite
|
Sign up to set email alerts
|

Cement augmentation of the navigated iliosacral screw in the treatment of insufficiency fractures of the sacrum. A new method using modified implants

Abstract: Purpose Pelvis ring fractures of geriatric patients are currently a serious problem in orthopedic and trauma surgery. One controversy that remains is the insufficiency fracture of the sacrum with treatment options ranging from conservative to operative. We modified standard 7.3-mm screws with additional perforations at the tip to allow cement injection trough the screw to improve implant anchorage. Method We describe a new method of treatment of sacral insufficiency fractures. We use modified cannulated 7.3-mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 17 publications
2
62
0
6
Order By: Relevance
“…Preliminary clinical studies showed a decrease in implant loosening rates with cement augmentation in the osteoporotic proximal femur [20] and spine [38]. Cement augmentation of sacroiliac screw fixation has been reported in small case reports and series [41,46], and few complications were reported.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary clinical studies showed a decrease in implant loosening rates with cement augmentation in the osteoporotic proximal femur [20] and spine [38]. Cement augmentation of sacroiliac screw fixation has been reported in small case reports and series [41,46], and few complications were reported.…”
Section: Discussionmentioning
confidence: 99%
“…The implant purchase may be enhanced by increasing the bone-implant contact area using modificated screws and techniques [7][8][9][10][11], or by the application of bone cement [12][13][14]. The use of cement-augmentation of standard iliosacral screws has been reported earlier [25], with promising preliminary outcomes noted when employing the use of iliosacral screws with perforations at the tip of the screws [26]. Based on our presented results, placement of screw perforations can be recommended also at the center of the screw to allow for additional cement application, especially at the lateral mass of the sacrum where a significantly diminished bone quality is expected.…”
Section: Discussionmentioning
confidence: 99%
“…Due to lower screw anchorage, there is a higher risk of screw loosening with recurrent instability in the posterior pelvic ring (41). To enhance screw anchorage in the trabecular bone of the upper sacrum, cement augmentation of the iliosacral screws has been described (42). The technique is different from sacroplasty, where the cement is applied in the fracture gap.…”
Section: Introductionmentioning
confidence: 99%
“…Biomechanical studies have shown that stability of iliosacral screw fixation in FFP is significantly higher with cement augmentation than without (44,45). Clinical experience is still small, but results are promising (42,43).…”
Section: Introductionmentioning
confidence: 99%